Development of metropolitan police emergency call system - Tunlawat Narongsak (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The objectives of this research were to investigate the problems and obstacles of the metropolitan police emergency call and to develop the most appropriate foreign model for metropolitan police emergency call and patrol planning and the best model for metropolitan police emergency call and channels of emergency report. In this research, quantitative and qualitative methods were employed. A sample of police officers in 500 units and 100 victims were used for the quantitative method, and focus group was conducted with patrol and special force police officers in 25 units, and an interview was carried out with senior police officers in 12 units. The results revealed that metropolitan police emergency call technology systems were outdated which resulted in failed operations. Buildings and facilities were not suitable for work and operation. People were lack of knowledge in law and police tactics. Police officers who took operations were in shortage of budget for acquiring tools and equipment for effective actions. A victim or injured person may call for police, ambulance and fire truck foreign police emergency call free of charge. It is recommended that emergency call should be integrated in one center called "National Police Emergency Call Center" for the effectiveness of the metropolitan police emergency call using. Moreover, metropolitan police center should include other projects such as Miracle Eyes and Police I Lert You. Also, social media should be utilized for complaints and promotion of new technology for people's awareness